IDENTIFIKASI BAKTERI ASAM LAKTAT DARI KOMBUCHA ROSELLA - Merkuria - Karyantina; Sumarmi Sumarmi (AGROINTEK, 2021)
Kombucha is one type of traditional fresh drink derived from fermented sweet tea water for 7-10 days. Bacteria play a role in the kombucha fermentation process are acetic acid acid bacteria and lactic acid bacteria. This study aims to isolation and identification lactic acid bacteria that play a role in the kombucha rosella fermentation. The study was conducted using De Man, Rogosa and Sharpe media to add CaCO3 1 %. Colonies that grow and provide clear zones are purified several times to obtain uniform colonies morphologically and biochemically. The 18 isolates identified 8 isolates that have the characteristics of lactic acid bacteria. Analysis with API 50CH KIT identified 4 isolates from the genera Lactobacillus and 4 isolates from the genus Lactococcus.